Advancing environmentally sustainable learning health systems: Perspectives from a Canadian health center - Brittany V. Barber; Douglas Sinclair; Christine Cassidy (Learning Health Systems)
Abstract Background There is increasing demand for health systems to reduce greenhouse gas emissions and invest in climate‐resilient health care. Coordinating organizational structures and processes for reducing health system emissions presents challenges. Learning health systems, defined as systems that seek to continuously generate and apply evidence, innovation, quality, and value in health care, can guide health systems with planning organizational structures and processes to advance environmentally sustainable healthcare. The purpose of this research is to gather in‐depth insight from key health system leaders and healthcare professionals to identify challenges and recommendations for planning environmentally sustainable learning health systems. Methods Environmental scan methods were used, comprising jurisdictional literature review and informal discussions with key informants at one tertiary care center in Nova Scotia, Canada. Key informants were asked to describe challenges of coordinating environmentally sustainable health system structures and processes, and recommendations to advance planning for environmentally sustainable learning health systems. Deductive thematic analysis was used to categorize challenges and recommendations into seven characteristics of a learning health system framework. Results Informal discussions with 16 key informants provide detailed descriptions of 7 challenges and recommendations for planning and coordinating organizational structures and processes to advance environmentally sustainable learning health systems. Health system challenges include limited patient and community engagement, no systematic approach to measuring and monitoring emissions data, and limited knowledge of sustainability co‐benefits and strategies for mobilizing sustainable organizational change. Recommendations include engaging patients and communities in co‐creation of sustainable healthcare, monitoring of emissions data identifying high‐impact areas for action, and well‐coordinated leadership supporting sustainable policies, procedures, and decision‐making in practice. Conclusion Learning health systems provide structure for establishing critical processes to adapt to routinely collected data through rapid cycle improvements, and operationalization of value‐based health care that prioritizes health outcomes, reduction of costs, and mitigating environmental impacts.